TlPOLOGI BANGUNAN RUMAH TINGGAL ADAT SUNDA DI KAMPUNG NAGA JAWA BARAT (Building Typology of Sundanese Traditional Houses at Kampung Naga, West Java) - Ilham, Anggie Nur; SB, Afriyanto Sotyan (Tesa Arsitektur, 2012)
A traditional house has specific characteristics that differ from one place to another. The house is treated as one of cultural heritages that should be protected and conserved. Thats why it is vety important to study traditional houses and one of such houses is Sundanese traditional houses at Kampung Naga, West Java. Kampung Nagas houses are characterized by poled or staged houses that are built in a group so that it makes a traditional kampong or village that is in habited by a group of people that strongly keep customs inherited by their ancestors. The specific characteristics of these traditional houses are of their building typology and interior design pattern. This writing will expose the building typology of Sundanese traditional houses at Kampung Nagas settlement. Typology here means the characteristics of the shape of Sundanese traditional house in a whole. The data gathering method covers field survey, libraty study, and internet browsing.